2021
DOI: 10.3389/fendo.2021.752995
|View full text |Cite|
|
Sign up to set email alerts
|

Ankle-Brachial Index Is Independently Associated With Cardiovascular Outcomes and Foot Ulcers in Asian Patients With Type 2 Diabetes Mellitus

Abstract: Background and AimsThe ankle-brachial index (ABI) is an efficient tool for objectively documenting the presence of lower-extremity peripheral arterial disease (PAD). The predictive factors of cardiovascular events and diabetic foot ulcer were not clear from the ABI examination in Taiwanese patients with type 2 diabetes mellitus (DM).MethodsWe enrolled 482 patients with type 2 DM who regularly visited the outpatient department of Chang Gung Memorial Hospital and received ABI as well as brachial-ankle pulse wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Although this research has a significant contribution to knowledge, there are some limitations to this research. Diabetic foot ulcers can be detected in various ways, including checking blood glucose, HbA1c (Miranda, Da Ros, and Marfella 2021), ankle brachial index (ABI) (Yang et al 2021), monofilament examination (Baldursdottir et al 2020), TcPO2 . examination (Fagher and Löndahl 2021) as well as regular foot checks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this research has a significant contribution to knowledge, there are some limitations to this research. Diabetic foot ulcers can be detected in various ways, including checking blood glucose, HbA1c (Miranda, Da Ros, and Marfella 2021), ankle brachial index (ABI) (Yang et al 2021), monofilament examination (Baldursdottir et al 2020), TcPO2 . examination (Fagher and Löndahl 2021) as well as regular foot checks.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise can also improve motor function so that it can reduce the risk of falling (Dai and Li 2019) which can cause ulcers. Exercise can also increase Ankle-Brachial Index, because Diabetics with a low Ankle-Brachial Index have a higher risk of developing foot ulcers (Yang et al 2021). For this reason, it is important to carry out routine Ankle-Brachial Index examinations to detect peripheral arterial diseases and angiography to prevent amputations (Ravidas, P., and G. 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since amputation risk of lower extremities is a common complication of patients with PAD and diabetes ( 230 ), it is important to be able to assess PAD risk among diabetic patients before they develop diabetic foot ulcers in which amputation then becomes more necessary. One major indicator of amputation risk that can be non-invasively assessed is by determining the ankle brachial index ( 231 ). The results of this study showed that patients who exhibited a lower ankle brachial index were at a higher risk for a foot ulcer and thus an amputation.…”
Section: Cardiovascular and Other Complications In Diabetesmentioning
confidence: 99%
“…There are many methods to check LEAD. Among them, ABI, as the preferred screening method for LEAD in diabetes, is simple and inexpensive, and can be used to predict diabetic foot and cardiovascular and cerebrovascular diseases ( 5 ). However, due to the influence of vascular calcification, its sensitivity in the examination of LEAD in diabetes is not high ( 6 ).…”
Section: Introductionmentioning
confidence: 99%